Kazán jelleggörbe elemzése hőkezelési folyamat optimalizálásához - Fabulya, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The quality and rentability o f preserved food (besides the quality o f the basic m aterials, the good recipe, the features o f the production belts) are determined by their h eat-treatm ent and its organization. The production process w hich was not planned carefully can im ply quality problem s and considerable increase of expenses. To support work organization with com puter has not been in practice in H ungary so far. M y main objective in case o f technologies w ith an autoclave group is to elaborate a program system based on sim ulation which could help reduce th e direct costs o f heat- treatm ent and improve the quality o f products. For this objective it is necessary to carry out further sub-tasks and exam inations w hose results should be utilized in the system. O ne o f these is to analyse w ith sim ulation the load-dependent efficiency graph o f gas boiler w hich provides the necessary amount o f steam and then to use the results to find the conditions o f optim al o peration and to calculate costs reduction arising from it